2018
DOI: 10.1021/acs.inorgchem.7b02513
|View full text |Cite
|
Sign up to set email alerts
|

Iridium(III)-Based Metal–Organic Frameworks as Multiresponsive Luminescent Sensors for Fe3+, Cr2O72–, and ATP2– in Aqueous Media

Abstract: Three iridium(III)-based metal-organic frameworks (MOFs), namely [Cd{Ir(ppy-COO)}(DMF)(HO)]·6HO·2DMF (1), [Cd{Ir(ppy-COO)}(DMA)(HO)]·0.5HO·2DMA (2), and [Cd{Ir(ppy-COO)}(DEF)(HO)]·8HO·2DEF (3) (ppy-COOH = methyl-3-(pyridin-2-yl)benzoic acid, DMF = N,N-dimethylformamide, DMA = N,N-dimethylacetamide, DEF = N,N-diethylformamide), have been synthesized and characterized. Single-crystal structural determinations reveal that compounds 1-3 are isostructural, showing a three-dimensional framework structure with (3,6) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
45
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 113 publications
(47 citation statements)
references
References 95 publications
2
45
0
Order By: Relevance
“…dimethylacetamide and DEF is N,N-diethylformamide) were recently reported by Zheng and co-workers [143]. X-ray single-crystal structure analyses revealed that MOF11, MOF12 and MOF13 are isostructural and crystallized in the monoclinic space group P2 1 /n, showing a three dimensional framework where complex L1 bridges three Cd 2+ ions through its six carboxylate oxygen atoms…”
mentioning
confidence: 75%
“…dimethylacetamide and DEF is N,N-diethylformamide) were recently reported by Zheng and co-workers [143]. X-ray single-crystal structure analyses revealed that MOF11, MOF12 and MOF13 are isostructural and crystallized in the monoclinic space group P2 1 /n, showing a three dimensional framework where complex L1 bridges three Cd 2+ ions through its six carboxylate oxygen atoms…”
mentioning
confidence: 75%
“…S17 †), a linear presented at lower and higher experimental concentration range (0-20 mM; 36-90 mM), and the K SV and LOD values were 1.31 AE 0.01 Â 10 4 M À1 , 1.09 AE 0.02 Â 10 5 M À1 , respectively, displaying the high quenching efficiency of the Fe 3+ ions. [48][49][50] In addition, the LODs based on Tb 3+ @Cd-P were also obtained and 0.66 AE 0.02 mM for Fe 3+ ions.…”
Section: Detection Of Ionsmentioning
confidence: 83%
“…The organometallic iridium centres adopt distorted-octahedral geometries [Ir-C: 1.998, Ir-N: 2.118 Å] (Table S2), similar to those reported in other heterometallic Ir-M coordination polymers. 30 The [Ir(ppy-COO) 3 ] 3organometallic ligands are arranged on opposite sides of the anionic layer where one enantiomer with one polarity takes one face the other enantiomer with the opposite polarity on the other face ( Figure 1). The resulting layer is neither chiral nor polar and a centrosymmetric cell is formed.…”
Section: Resultsmentioning
confidence: 99%